ASSESSMENT OF CASTING DEFECTS BY RADIOGRAPH INTERPRETATION-A REVIEW - S.A.Kekade; R.M.Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
The major objective of radiographic testing of castings is the disclosure of defects that adversely affect the strength of the product. Castings are a product form that often receive radiographic inspection since many of the defects produced by the casting process are volumetric in nature, and are thus relatively easy to detect with this method. These discontinuities of course, are related to casting process deficiencies, which, if properly understood, can lead to accurate accept-reject decisions as well as to suitable corrective measures. Since different types and sizes of defects have different effects of the performance of the casting, it is important that the radiographer is able to identify the type and size of the defects. The castings used to produce the standard radiographs have been destructively analyzed to confirm the size and type of discontinuities present. The following is a brief description of the most common discontinuity types included in existing reference radiograph documents (